Determinants of Tissue PCO₂ in Shock and Sepsis: Relationship to the Microcirculation - Dubin, Arnaldo (2009)
The development of gastrointestinal tonometry was an important step in the monitoring of tissue dysoxia. It rapidly became a useful tool in basic research. In addition, and for the first time, a regional parameter could be used to detect and to treat hypoperfusion. From an experimental point of view, tonometry adequately tracks intramucosal acidosis, i.e., the increase in intramucosal-arterial PCO2 difference (ΔPCO2). Likewise, the increase in ΔPCO2 is better than other systemic and intestinal variables to show tissue hypoperfusion in normal volunteers and in experimental models. Intramucosal acidosis is a sensitive predictor of gastric and colonic mucosal ischemia. Furthermore, gastric tonometry is an insightful predictor of outcome. This usefulness has been shown in postoperative, critically ill, septic and shock patients. Gastric tonometry might also be used to assess the effect of vasoactive drugs. Finally, intramucosal pH (pHi) has been evaluated as a guide for resuscitation. Gutierrez et al. demonstrated in a randomized controlled trial that pHi-guided therapy could decrease mortality in critically ill patients.